Pengaruh Job Insecurity Terhadap Turnover Intention Melalui Stres Kerja Sebagai Variabel Mediasi (Studi Kasus Pada Karyawan PT Spice Agro International) - Afrianto, Kharist (Peneliti.net, 2023)
The purpose of this study was to test and analyze the effect of job insecurity on turnover intention with work stress as a mediating variable for employees of PT Spice Agro International. This research causality study with a quantitative approach. The sampling technique used non-probability sampling with purposive sampling in which the sample was determined by the researcher with a total of 36 respondens at PT Spice Agro International. The statistical analysis used in this research is partial least squares (PLS) with the help of SmartPLS 3.2.9 software. The results of this analysisi obtained from this study indicate that job insecurity has a positive and significant effect on turnover intention, job insecurity has a positive and significant effect on work stress, job stress has a positive and significant effect on turnover intention, job stress is able to mediate the effect of job insecurity on turnover intention.